The 5 year outcomes of patients receiving haemodialysis versus peritoneal dialysis at Groote Schuur Hospital, Cape Town, South Africa - Crombie, Kenneth (Department of Medicine, 2019)
Background: Despite the rising global prevalence of chronic kidney disease, dialysis remains restricted in South Africa and acceptance onto many renal replacement programs is limited to those suitable for transplantation. Few studies exist comparing survival outcomes of peritoneal dialysis [PD] and haemodialysis [HD] patients from developing countries. In addition, data of those switching to HD are conflicting. Methods: This retrospective cohort study compares survival outcomes of patients receiving HD or PD at Groote Schuur Hospital, South Africa, from 2010- 2015. Results: 174 patients were assigned to HD and 189 to PD, of which 42 switched to HD. The majority (68.31%) of patients were under 45 years. More black Africans received HD. The most common causes of death were infection (26%) and fluid overload (19%). Having removed those PD patients for whom modality switch was denied due to contraindications to transplantation, survival probability at 1-, 2- and 5- years for HD versus PD was 98.68% (CI: 94.84-99.67), 96.95 (CI: 91.98-98.86) and 83.52% (CI: 71.75-90.70) versus 96.73% (95% CI: 92.32- 98.63), 89.95 (95% CI: 83.17- 94.1) and 76.69 (95% CI: 60.97- 86.73) respectively. (p= 0.145) The survival probability of those patients who switched from PD to HD, for the same intervals was 100%, 97.37% (95% CI: 82.75-99.63) and 97.37 % (95% CI: 82.75-99.63). (p=0.001) Conclusion: In this setting, PD is not inferior to HD and those patients switching from PD to HD have the best survival outcomes. Therefore, the current local PD first policy is justified, although interventions should be aimed at improving outcomes.